A 1.1 Million Base Pair X-Chromosomal Deletion Covering the PDHA1 and CDKL5 Genes in a Female Patient with West Syndrome and Pyruvate Oxidation Deficiency - Mayr, Johannes A.; Koch, Johannes; Fauth, Christine; Zimmermann, Franz A.; Rauscher, Christian; Zschocke, Johannes; Sperl, Wolfgang (Neuropediatrics, 2012)
Mutations in the X-linked E1α subunit of the pyruvate dehydrogenase complex (PHDC) are the most frequent causes of PDHC deficiency. The clinical picture is heterogeneous depending on residual enzyme activity and X-inactivation. We report on a girl who presented at an age of 3 weeks with muscular hypotonia, vomiting, hyperlactatemia, microcephaly, enlarged ventricles, partial agenesis of the corpus callosum, and seizures. PDHA1 sequencing was normal in DNA from blood. In muscle, normal PDHC activity was measured while substrate oxidation rates revealed moderately diminished pyruvate oxidation. Quantitative PCR analysis revealed hemizygosity of the whole PDHA1 gene. Homozygosity mapping and determination of the breakpoint showed a 1.1 million base pair deletion on the X-chromosome including the CDKL5 and PDHA1 genes. The difficulty in the diagnosis of PDHC deficiency is evident: (1) enzyme activity can be normal depending on the X-inactivation; (2) large deletions can be missed by routine genetic analysis; and (3) only quantification of the PDHA1 gene content revealed the mutation in our patient. We recommend to revisit patients who are clinically suspicious for a mitochondrial disorder especially for hidden PDHA1 mutations, such as large deletions.
Keywords: pyruvate dehydrogenase complex deficiency; mitochondrial disease; epilepsy; CDKL5; X-inactivation